2020
DOI: 10.1002/ppul.24623
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth delivery of adherence and medication management system improves outcomes in inner‐city children with asthma

Abstract: Healthcare disparities exist in pediatric asthma in the United States. Children from minority, low‐income families in inner‐city areas encounter barriers to healthcare, leading to greater rates of poorly controlled asthma and healthcare utilization. Finding an effective way to deliver high‐quality healthcare to this underserved population to improve outcomes, reduce morbidity and mortality, and reduce healthcare utilization is of the utmost importance. The purpose of this study was to assess the feasibility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
3
45
0
2
Order By: Relevance
“…29,30 Strategies associated with telerehabilitation, such as phone calls, text messaging and video communications, are low-cost reasonable strategies that could help improve rates of adherence to exercises. 31,32 In addition, the results demonstrated that most demographic and clinical factors were not associated with adherence, which is in accordance with Dalcin et al 20 promote changes in self-awareness related to exercise practice, which could minimize the lack of interest, motivation, time, and tiredness. 29,30 Health education, provided by video animations and infographics, may inform about disease prognosis and benefits of exercises, which could minimize noncommitment and doubts regarding short-and long-term effects of exercises.…”
Section: Discussionsupporting
confidence: 85%
“…29,30 Strategies associated with telerehabilitation, such as phone calls, text messaging and video communications, are low-cost reasonable strategies that could help improve rates of adherence to exercises. 31,32 In addition, the results demonstrated that most demographic and clinical factors were not associated with adherence, which is in accordance with Dalcin et al 20 promote changes in self-awareness related to exercise practice, which could minimize the lack of interest, motivation, time, and tiredness. 29,30 Health education, provided by video animations and infographics, may inform about disease prognosis and benefits of exercises, which could minimize noncommitment and doubts regarding short-and long-term effects of exercises.…”
Section: Discussionsupporting
confidence: 85%
“…Specific key findings in this study by Lin et al 15 that may help direct future work needed to scale such an approach include: (a) it is critical to engage stakeholders outside the research team early and consistently to ensure needs are met and barriers are addressed; (b) children with more severe asthma appear to experience the most improvement; (c) improvements in outcomes appeared early in the intervention suggesting a less intense medical visit schedule could be considered; (d) improvements in adherence were modest overall and not sustained beyond the intensive self‐management visits suggesting ongoing attention to adherence will be important to long term success.…”
mentioning
confidence: 51%
“…A recent Cochrane review 13,14 identified key benefits of school‐based asthma management programs, including reducing the number of acute episodes of health care use and days of restricted activity for students. A new study by Lin et al 15 takes an innovative approach to school‐based care by integrating video‐based telehealth medical and self‐management visits with electronic inhaler monitoring to improve asthma outcomes. In this uncontrolled pilot study designed to test feasibility and efficacy, 21 children with uncontrolled asthma were recruited from urban, low‐income schools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Across these studies, significant improvements in asthma and COPD outcomes have been demonstrated in association with their use, including reduction in daytime and night-time self-reported symptoms 15 , reduction in SABA use 13,25 , increase in the number of SABA-free days 12,13 , improvement in asthma control as measured by the ACT 26,27 , and improvement in adherence to controller medications [28][29][30][31] . These benefits have been observed in diverse participants, including underserved patients with both asthma and COPD 13,26 . Significant reduction in acute healthcare utilization, including ED visits and hospitalization events, has been demonstrated for both asthma and COPD 27,29,32 .…”
Section: Clinical Benefit Of Respiratory Monitoringmentioning
confidence: 99%